Deposition of nanostructured fluorine-doped hydroxyapatite-polycaprolactone duplex coating to enhance the mechanical properties and corrosion resistance of Mg alloy for biomedical applications - Bakhsheshi-Rad, H. R. (Elsevier Ltd, 2016)
The present study addressed the synthesis of a bi-layered nanostructured fluorine-doped hydroxyapatite (nFHA)/polycaprolactone (PCL) coating on Mg-2Zn-3Ce alloy via a combination of electrodeposition (ED) and dip-coating methods. The nFHA/PCL composite coating is composed of a thick (70-80 μm) and porous layer of PCL that uniformly covered the thin nFHA film (8-10 μm) with nanoneedle-like microstructure and crystallite size of around 70-90 nm. Electrochemical measurements showed that the nFHA/PCL composite coating presented a high corrosion resistance (Rp = 2.9 × 103 kΩ cm2) and provided sufficient protection for a Mg substrate against galvanic corrosion. The mechanical integrity of the nFHA/PCL composite coatings immersed in SBF for 10 days showed higher compressive strength (34% higher) compared with the uncoated samples, indicating that composite coatings can delay the loss of compressive strength of the Mg alloy. The nFHA/PCL coating indicted better bonding strength (6.9 MPa) compared to PCL coating (2.2 MPa). Immersion tests showed that nFHA/PCL composite-coated alloy experienced much milder corrosion attack and more nucleation sites for apatite compared with the PCL coated and uncoated samples. The bi-layered nFHA/PCL coating can be a good alternative method for the control of corrosion degradation of biodegradable Mg alloy for implant applications.